Effect of a Drug-Eluting Stent vs. Bare Metal Stent for the Treatment of Symptomatic Intracranial and Vertebral Artery Stenosis - Si, Jiang-Hua; Ma, Ning; Gao, Feng; Mo, Da-Peng; Luo, Gang; Miao, Zhong-Rong (Frontiers in Neurology, 2022)
Background: For patients with symptomatic intracranial and vertebral artery stenosis who receive endovascular treatment, in-stent restenosis (ISR) is associated with the recurrence of ischemic stroke. This study evaluated a drug-eluting stent (DES) vs. bare metal stent (BMS) for the treatment of symptomatic intracranial and vertebral artery stenosis. Methods: This clinical trial has been registered with registration number ChiCTR2200055925.The trial was a multicenter, 1:1 randomized, prospective feasibility clinical trial with 10 participating centers in China from March 2014 to October 2015. Eligible patients had symptomatic intracranial and vertebral artery stenosis (70%-99%) and had medical drug treatment failure. The primary end point was the rate of in-stent restenosis at 180 days of randomization. The secondary end point was a composite of 2 outcomes: (1) ischemic stroke or transient cerebral ischemia (TIA) in the same territory as the presenting event (distal to the target lesion) between 30 days and 1 year after randomization and (2) successful stent implantation. Results: We enrolled 188 patients at 10 medical centers in China (92 assigned to the DES group and 96 to the BMS group). There were 28 patients (43.8%) with an ISR at 180 days in the BMS group and 10 patients (14.5%) in the DES group (risk difference, 29.3% [95% CI, 14.5%-44.0%]; P =0.001). The percent of patients with ischemic stroke or TIA in the same territory between 30 days and 1 year was 5.2% (5/96) in the BMS group and 2.2% (2/92) in the DES group (risk difference, 3.0%; [95% CI, -2.3% to 8.2%]; P = 0.354). The percent of patients with successful stent implantation was 99.0% (95/96) in the BMS group and 97.8% (90/92) in the DES group (risk difference, 1.1%; [95% CI, -1.7% to 3.9%]; P = 0.584). Conclusions: Among patients with symptomatic intracranial arterial stenosis and vertebral artery stenosis, the use of a drug-eluting stent compared with a bare metal stent resulted in a decreased risk of ISR, similar successful stent implantation, and similar adverse events. These findings support the use of a drug-eluting stent for patients with symptomatic intracranial arterial stenosis and vertebral artery stenosis.